Aerial flow in a vertical cylindrical container with thermal gradient under a vertical magnetic field. (6th April 2005) - Akamatsu, Masato; Higano, Mitsuo; Ozoe, Hiroyuki
This study focuses on how magnetising force affects the convection of air in a vertical cylindrical container with thermal and magnetic field gradients in non-gravitational and gravitational fields. The model systems with three different thermal boundary conditions are considered in the present work and numerical computations were carried out by changing the relative location of an electric coil and container. In a non-gravitational field, the aerial flow was induced by the magnetising force. On the other hand, in a gravitational field, the air was driven by both gravitational and magnetising forces. In both fields, flow pattern and heat transfer rate greatly depended on the axial location of the electric coil. Under the specific numerical condition, the pulsating flow was observed by the coupling of gravitational and magnetising forces. These phenomena could be successfully explained by visualising the field of magnetising force and considering the mass magnetic susceptibility of air according to Curie's law.